PP-37 Developing paediatric antimicrobial doses for the new zealand formulary for children. Issue 10 (20th September 2017) - Simpson,; Young,; Herd,; Ferguson,; Broughton,; Tilyard,; Reith,
Abstract : Background: Many antimicrobial medications for chil-dren are used outside of the product license and prescrib-ers encounter a lack of evidence-based dosing guidance. The New Zealand Formulary for Children (NZFC) devel-oped a process to provide antimicrobial guidance based on the best available evidence from regulatory data, pro-fessional guidelines, clinical experience and clinical con-sensus. Methods: Indications and doses for antimicrobial med-ications in the NZFC were originally derived from the British National Formulary for Children (BNFC). A clinical advisory group (CAG) from New Zealand's national paedi-atric hospital was recruited to provide guidance relating to NZFC antimicrobial monographs. The CAG consisted of two paediatric infectious disease physicians and an antimicrobial stewardship pharmacist. The CAG identified monographs requiring review, and proposed changes to make theses more suited to New Zealand practice. NZFC clinical editors then compared the proposed alterations against the New Zealand approved medicine datasheet (NZAMD). If these did not agree, comparison with rep-utable resources such as New Zealand guidelines, in-ternational guidelines, and recognised references used in the clinical field. When supporting evidence was not available, the clinical editors sought further input from the CAG. Any indications and/or doses differing from the NZAMD were identified in the NZFC monographs. Results: A total of 119 antimicrobial medications in the NZFC were identified as requiring review. Following re-view, 77 (65%) medications had indication and/or dosing information as unlicensed/unapproved. Of these 35 had no corresponding NZAMD information, 20 recommend-ed doses outside the NZAMD age ranges, 15 included indications not stated in the NZMAD, 5 with dosing dif-ferent to that in the NZAMD and 5 with an unapproved administration route Conclusion: For a national formulary to be able to pro-vide suitable antimicrobial dosing in children, collabora-tion with national experts is essential. Validating dosing against reputable resources is an important step when providing unlicensed dosing to a recognised standard.